Interactive integration into magazine cover designs (Al-Academy, 2023)
Interactive integration is a modern communication method used by the designer to convey ideas, as well as combines the aesthetic pleasure of the recipient because of its flexibility in merging sound with image in order to deliver an advertising message, whether news or illustrative. The research problem is summarized by the following question: What is interactive integration in the design of magazine covers? The importance of the research comes as it sheds light on the issue of interactive integration from an intellectual and practical point of view.The theoretical framework dealt with two sections, the first is interactive integration, and the second topic: designing magazine covers, with indicators for this theoretical framework.1. The interactive integration in the advertisement contributes to attracting and arousing the interest of the recipient towards the direction of the advertisement, as well as its clarity and readability.2. The diversity of the use of digital images and animation has a role in highlighting the interactive integration through the various color values and the overall harmony within the design components.Keywords: integration, interaction, designs, magazine covers